Structural Electrical and Magnetic Properties of La2/3ca1/3mno3 Perovskites With In, Ga And Al Substitution at Either La Or Ca Site - Chik, Abdullah (2004)
The structure, electrical and magnetic properties of colossal magnetoresistance material La2/3Cal13Mn0(3L CMO) substituted with In, Ga and A1 at both La and Ca site have been studied. Samples of (La1.,In,)2/~Cal/~MnO~(L ICMO), (Lal. ,GaX)2nCalnMnO3 (LGCMO), (Lal-,A1,)213Cal/3Mn03 (LACMO), La2n(Cal- ,InX)lmMn03 (LCIMO), Lazn(Cai-xGax)1/3Mn03 (LCGMO), Lam (Cal-,AlX)lnMnO3 (LCAMO) with x=O.O to 1.0 were prepared using solid state reaction method. X-ray diffraction (XRD) patterns shows single phase pattern at low concentration with increasing intensity of secondary phases at high concentration of dopant. All samples except sample LICMO x=0.6, exhibit orthorhombic structure. Sample LICMO x=0.6 exhibits tetragonal structure. The AC susceptibility studies indicates LICMO, LGCMO, LACMO exhibit wide variety of magnetic phases. For LICMO, LACMO and LGCMO system, ferromagnetic to paramagnetic transition are observed from the undoped sample x=O.O to 0.5,0.4 and 0.3 respectively. With further doping at La site, spin glass transition is observed followed by antiferromagnetic to paramagnetic transition with increasing dopant concentration. The Curie temperature, Tc decreases as indium, gallium and aluminum doping increases indicates weakening of ferromagnetic interactions, but the antiferromagnetic interactions is getting stronger with increasing dopant, resulting spin glass system and antiferromagnetism with further doping concentration. With In, Ga and Al substitution at the Ca site, all samples with the exception of LCIMO x=1 .O, exhibit ferromagnetic to paramagnetic transition. For LCIMO sample x=1.0, AC susceptibility study indicates antiferromagnetic to paramagnetic transition. The electrical properties show the metal to insulator transition and this property is limited to certain doping level for both La and Ca site substitution, i.e. until x=0.9 for LICMO, x=0.8 for LGCMO, LACMO, LCIMO and LCGMO, and x=0.5 for LCAMO system. Beyond the specific doping level, the samples become insulator for La site substitution, and semiconducting behaviour for Ca site substitution. This phenomenon is due to the ionic size of dopant for La site substitution, and both ionic size of dopant and decreasing Ivln4+/Mn3+ra tio due to decreasing ca2+ ions. Fitting of adiabatic small polaron hopping model to high temperature ln(R/T), indicates the activation energies of all samples within range of 0.03eV to 0.17eV which is consistent with reported values in the literature, confirming small polaron hopping activities beyond Tp. Magnetoresistance measurements show that magnetoresistance (MR) ratio is maximum at temperature close to Tp for all samples, and increases with increasing dopant concentration for La site substitution. However, for Ca site substitution, the magnetoresistance's maximum is not as high as La site substitution, and decreases with increasing dopant concentration for x > 0.3, because of the low ~ n ~ + / I v frnat~io+ t hat weakened the Zener double exchange interactions and thus the metallic conductivity and ferromagnetism. High MR values are 80% for LICMO sample x=0.4, 95% for LGCMO sample x=0.6 and 87% for LACMO sample x=0.2, compares to 40% of LCMO sample. The Scanning Electron Microscopy (SEM) micrographs indicate fused and denser grains for all samples. Large abnormal growth is seen only in LICMO for x=O.l and 0.2 samples and increasing level of porosity with increasing dopant is seen for LACMO, LCGMO and LCIMO samples. LICMO and LGCMO samples exhibit decreasing level of porosity with increasing substitution while LCAMO system has low level of porosity in all samples.